Twelve tips for enhancing student engagement - Peters, Harm (2019)
Student engagement refers to a broad range of activities where students participate in management, education, research, and community activities within their institutions. It is a mutually beneficial collaborative approach between students and their institutions. This article provides practical advice for the implementation or further development of student engagement at medical, dental, and veterinary schools. The tips provided are based on the experiences of a group of universities recently recognized for best practice in student engagement, and are supported by evidence from the literature. The tips cover overarching themes which include the creation of an institutional culture and formal framework for student engagement, and maximize communication routes between students with peers and faculty. Tips are for specific areas of active student engagement, covering curriculum design and development, peer teaching, governance processes, research activities, peer support programs, and interaction with the local community.